2010
DOI: 10.29333/ejgm/82886
|View full text |Cite
|
Sign up to set email alerts
|

Is There any Relationship Between Nasal Septal Deviation and Concha Bullosa

Abstract: Aim: To evulate relationship between nasal septal deviation and concha bullosa (CB) by using deviation angles and concha bullosa pneumatization index (CBPI). Method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…Patients with acute sinusitis, allergic sinusitis, asthma, cystic fibrosis, immune deficiency, metabolic diseases or malignant diseases or those who had previously undergone nasal or sinus surgery, or maxillofacial trauma cases, and children \8 years of age were excluded from the study [8].…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Patients with acute sinusitis, allergic sinusitis, asthma, cystic fibrosis, immune deficiency, metabolic diseases or malignant diseases or those who had previously undergone nasal or sinus surgery, or maxillofacial trauma cases, and children \8 years of age were excluded from the study [8].…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…The present study showed the presence of septum deviation in 24.6% of cases; in the literature, frequencies of septum deviation varying from 9% to 80% have been presented, depending on the population and methodology 4,5,13,14,[16][17][18][19] . Some authors mention septum deviation as the most common anatomical alteration in the nasal cavity 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms and skeletal variations due to NSD and CB are applicable and useful in the forensic context. These traits are common and have a complex pattern, as the literature reports a strong association between nasal concha hypertrophy and the side to which the nasal septum is diverted 4,11,13,14 . This research also aimed to verify and correlate the presence of CB and the possible correlation with NSD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations